Unjuk kerja catalytic converter katalis tembaga krom terhadap penurunan temperatur emisi bas buang motor bensin - RM Bagus Irawan; Edi Pujianto; Muh Faishal Khairi (University of Muhammadiyah Jakarta, 2022)
Catalytic Converter is a technology used to reduce air pollution which is installed in the exhaust gas (muffler) of gasoline motorized vehicles. This Catalytic Converter serves to accelerate the oxidation of Hydrocarbon (HC) and Carbon Monoxide (CO) gas emissions, as well as to reduce Nitrogen Oxide (NOx). Changes in exhaust emissions mentioned above are strongly influenced by the working temperature of the Catalytic Converter. Chrome Copper metal material as a catalyst material, will be investigated and tested on a laboratory scale, first to see the effect of changes in engine speed to temperature, secondly changes in temperature when using a Catalytic Converter with a Copper catalyst and thirdly changes in temperature when using a Chrome Copper Catalyst in the exhaust gas channel . The results of the study were first obtained that changes in engine speed affect the increase in temperature of the Catalytic Converter, the higher the engine speed the temperature rises and vice versa at low engine speed the temperature tends to decrease. The two installations of the Catalytic Converter caused the temperature to drop, at 3000 rpm engine speed (without the Catalytic Converter) the temperature was 317.5 ºC and fell to 227.36 ºC in 5 catalyst cells, 218 ºC in 10 cells and 230 ºC in 15 cells. (with Cu Catalytic Converter). Whereas in the installation of a Chrome Copper Catalytic Converter, at 3000 rpm engine speed (without Catalytic Converter) the temperatur of 317.5 ºC drops to 237.5 ºC in 5 catalyst cells, 240.84 ºC in 10 cells and 249 ºC in 15 cells, where the decrease in temperatur that occurs is higher with the use of a copper catalyst.